Optical response of the Cu2S2diamond core in Cu2II(NGuaS)2Cl2 - Witte, Matthias; Grimm-Lebsanft, Benjamin; Goos, Arne; Binder, Stephan; Rübhausen, Michael; Bernard, Martin; Neuba, Adam; Gorelsky, Serge; Gerstmann, Uwe; Henkel, Gerald; Schmidt, Wolf Gero; Herres-Pawlis, Sonja (Journal of Computational Chemistry)

Surface vibrational Raman modes of In:Si(111)(4×1)and(8×2)nanowires - Speiser, E.; Esser, N.; Wippermann, S.; Schmidt, Wolf Gero (Physical Review B)

Temperature-Dependent Hole Mobility and Its Limit in Crystal-Phase P3HT Calculated from First Principles - Lücke, Andreas; Ortmann, Frank; Panhans, Michel; Sanna, Simone; Rauls, Eva; Gerstmann, Uwe; Schmidt, Wolf Gero (The Journal of Physical Chemistry B)

Inhomogeneous and Homogeneous Line Broadening of Optical Spectra of PTCDA Molecules Adsorbed at Step Edges of Alkali Halide Surfaces - Paulheim, A.; Marquardt, C.; Aldahhak, Hazem; Rauls, E.; Schmidt, Wolf Gero; Sokolowski, M. (The Journal of Physical Chemistry C)

Grand canonical Peierls transition in In/Si(111) - Jeckelmann, Eric; Sanna, Simone; Schmidt, Wolf Gero; Speiser, Eugen; Esser, Norbert (Physical Review B)

Rare-earth silicide thin films on the Si(111) surface - Sanna, S.; Dues, C.; Schmidt, Wolf Gero; Timmer, F.; Wollschläger, J.; Franz, M.; Appelfeller, S.; Dähne, M. (Physical Review B)

Density functional theory of the CuA-like Cu2S2 diamond core in Cu 2II(NGuaS)2Cl2 - Witte, M.; Gerstmann, Uwe; Neuba, Adam; Henkel, G.; Schmidt, Wolf Gero (Journal of Computational Chemistry)

Atomic size effects studied by transport in single silicide nanowires - Miccoli, I.; Edler, F.; Pfnür, H.; Appelfeller, S.; Dähne, M.; Holtgrewe, K.; Sanna, S.; Schmidt, Wolf Gero; Tegenkamp, C. (Physical Review B)

A Bifunctional Electrocatalyst for Oxygen Evolution and Oxygen Reduction Reactions in Water - Schöfberger, Wolfgang; Faschinger, Felix; Chattopadhyay, Samir; Bhakta, Snehadri; Mondal, Biswajit; Elemans, Johannes A. A. W.; Müllegger, Stefan; Tebi, Stefano; Koch, Reinhold; Klappenberger, Florian; Paszkiewicz, Mateusz; Barth, Johannes V.; et al. (Angewandte Chemie International Edition)

Manipulation resolves non-trivial structure of corrole monolayer on Ag(111) - Tebi, Stefano; Aldahhak, Hazem; Serrano, Giulia; Schöfberger, Wolfgang; Rauls, Eva; Schmidt, Wolf Gero; Koch, Reinhold; Müllegger, Stefan (Nanotechnology)

Vergleichende Betrachtung von Software-Werkzeugen zur Geschäftsmodellentwicklung - Strotmeyer, Sebastian; John, Thomas; Kundisch, Dennis (Multikonferenz Wirtschaftsinformatik (MKWI))

Vergleich von Disambiguierungsansätzen bei Anforderungsbeschreibungen - Vollmers, Daniel

Delayed (de-)activation in servers with a sleep mode - Herlich, Matthias; Bredenbals, Nico; Karl, Holger (Sustainable Computing: Informatics and Systems)

Surface induced vibrational modes in the fluorescence spectra of PTCDA adsorbed on the KCl(100) and NaCl(100) surfaces - Paulheim, A.; Marquardt, C.; Sokolowski, M.; Hochheim, M.; Bredow, T.; Aldahhak, Hazem; Rauls, E.; Schmidt, Wolf Gero (Physical Chemistry Chemical Physics)
We report a combined experiment-theory study on low energy vibrational modes in fluorescence spectra of perylene-3,4,9,10-tetracarboxylic acid dianhydride (PTCDA) molecules.

Impurity-Mediated Early Condensation of a Charge Density Wave in an Atomic Wire Array - Yeom, Han Woong; Oh, Deok Mahn; Wippermann, Stefan; Schmidt, Wolf Gero (ACS Nano)

Fast Dynamic Fault Injection for Virtual Microcontroller Platforms - Adelt, Peer; Koppelmann, Bastian; Müller, Wolfgang; Becker, Markus; Kleinjohann, Bernd; Scheytt, Christoph (Proceedings of the IEEE/IFIP International Conference on VLSI (VLSI-SOC))
Electronic systems, like they are embedded in road vehicles, have to be compliant to functional safety standards like ISO 26262 [1], which limit the impacts of malfunctions for safety critical systems. ISO 26262, for instance, defines different safety levels for road vehicles, which require different means and measures for a safety compliant system and its development process like risk analysis and fault effect simulation. For fault effect simulation it is important to investigate the impact of physical and hardware related effects to the correct function of a system. This article first studies code and model mutations for fault injection in the context of fault effect simulation through different system abstraction levels. It demonstrates how high level mutations correlate to bit flips of software binaries by examples from the TriCore™ instruction set and finally presents a virtual platform based implementation for automated injection of bit flip based mutations into software binaries. Experimental results demonstrate the efficiency of the implemented approach.

An all-transmission-line 220 GHz differential LNA in SiGe BiCMOS - Mao, Yanfei; Schmalz, Klaus; Scheytt, Christoph; Shiju, E. (IEEE International Symposium on Radio-Frequency Integration Technology)
This paper presents a four stage all-transmission-line 220 GHz differential LNA in SiGe BiCMOS technology. Cascode topology is chosen for each stage. The amplifier takes advantage of microstrip transmission lines to realize the inductive load, Marshand balun, input, output, and inter-stage matching of the LNA. The LNA has a gain of 21 dB at 224 GHz, a 3 dB bandwidth of more than 6 GHz. It has a supply voltage of 3V and power dissipation of 234 mW. The amplifier is intended for the use in communication, security scanning, imaging and remote sensing at 220 GHz.

Fault Injection and Mixed-Level Simulation for Analog Circuits - A Case Study - Abughannam, Saed; Wu, Liang; Müller, Wolfgang; Scheytt, Christoph; Ecker, Wolfgang; Novello, Christiano (Analog 2016 - VDE)
The design of safety critical systems requires an efficient methodology for an effective fault effect simulation for analog and digital circuits where analog fault injection and fault effect simulation is currently a field of active research and commercial tools are not available yet. This article begins by discussing fault injection strategies for analog circuits applied on a case study with two topologies of a Voltage Controlled Oscillator (VCO). In the second part it performs on the basis of the example of a Wireless Sensor Network (WSN) node, how far different mixed level implementations with Verilog-A and SPICE can affect the simulation time and points out which component consumes the major part of the simulation time.

Obstacle detection using a miniaturized radar sensor operating at 120GHz ISM band - Nava, Federico; Genschow, Dieter; Scheytt, Christoph (DRONE Berlin 2016)
Currently, all drone manufactures face the same problem: flight safety utility will become mandatory to obtain the legal admission for broad commercial use of drones. This means that on-board obstacle detection and collision avoidance is a must-have in order to overcome existing legal barriers and acceptance issues. Some of the currently available sensors are too large, too heavy, or can be poorly integrated into existing systems. During the exhibition a demonstration of a novel micro-sensor operating at 120 GHz will be given and participants will have the chance to experience the device first-hand.

Linear ultra-broadband NPN-only analog correlator at 33 Gbps in 130nm SiGe BiCMOS technology - Javed, Abdul Rehman; Scheytt, Christoph; Von der Ahe, Uwe (IEEE Bipolar/BiCMOS Circuits and Technology Meeting)
An ultra-broadband analog correlator consisting of a four-quadrant multiplier and an ultra-fast resettable integrator using only NPN transistors was designed, fabricated, and measured. For the integrator, a cross-coupled transistor pair is used as a negative resistance generator. A novel ultra-fast reset circuit is implemented which allows to reset the integrator within very short time of 120 ps. The chip was fabricated using 130 nm SiGe BiCMOS technology with fT of 250 GHz and f max of 300 GHz. In the measurements carried out on printed circuit board, the correlator operated without noticeable performance degradation with inputs up to 33 Gbps which correspond to a bandwidth of more than 24 GHz. The correlator exhibits high linearity with output P1dB of more than 9.9 dBm (700 mV diff ) for both inputs. It dissipates 122.5 mW for the core circuit excluding the 50 Ω output driver. To the knowledge of the authors, the circuit represents the fastest analog correlator published so far. It can be used for spread spectrum communication, radar signal processing, and measurement applications.

Hierarchical Scheduling for Plug-and-Produce - Jatzkowski, Jan; Adelt, Peer; Rettberg, Achim (3rd International Conference on System-integrated Intelligence: New Challenges for Product and Production Engineering)
Today's increasing number of sensors and computation nodes covered by cyber physical systems (CPS) results in rising complexity. For instance, computation results are based on measured data whose quality strongly depends on their age. CPS therefore have real-time requirements on computation results and communication to keep temporal dependency between measured inputs and computed outputs. In addition, today's CPS shall be modular to enable flexibility and scalability, e.g., postulated for production systems in context of Industry 4.0. Enabling CPS to easily integrate components by some Plug-and-Produce mechanism is desired.In this paper, we aim at enabling Plug-and-Produce in CPS using hypervisor-based virtualization. This implies hierarchical scheduling of dependent real-time systems. Here, dependencies are given by precedence constraints of tasks. Based on an approach for detection of new components added to a real-time network, in this paper we focus on integration of enabled applications into the current schedule of a computation node. Here, enabled application refers to an application software that just got executable by plugging some component to the CPS. Applications are encapsulated by virtual machines and provide a self-description including information about required and provided data as well as timing behavior. This self-description is used to adjust global scheduling and thus include new functionality to the CPS.

Ultra-compact 122GHz Radar Sensor for Autonomous Aircrafts - Nava, Federico; Scheytt, Christoph; Zwick, Thomas; Pauli, Mario; Goettel, B.; Winkler, Wolfgang (3rd International Conference on System-Integrated Intelligence)
In this paper a prototype of an ultra-compact continuous-wave (CW) and frequency-modulated continuous-wave (FMCW) radar system using a highly-integrated radar chip and in-package antennas will be presented. An introduction will be given on the concept of antenna integration for millimeter-wave radar and the advantages of such systems. The radar then will be described in its main components, a 122 GHz Integrated Circuit including in-package antennas as well as the acquisition and processing system realized using flexible printed circuit board (FLEX PCB) technology. Furthermore initial measurements of the radar system will be presented and explained.

Some reflections on electromagnetic force in matter - Böcker, Joachim (2016 International Symposium on Power Electronics, Electrical Drives, Automation and Motion (SPEEDAM))

Local demand response and load planning system for intelligent domestic appliances - Stille, Karl Stephan Christian; Böcker, Joachim (2015 International Conference on Renewable Energy Research and Applications (ICRERA))

Integration of home photovoltaic generation into electricity tariff for load optimization - Stille, Karl Stephan Christian; Böcker, Joachim; Fröhleke, Norbert; Bettentrup, Ralf; Kaiser, Ingo (2016 4th International Istanbul Smart Grid Congress and Fair (ICSG))

Local grid load coordination for load-shiftable domestic appliances in a variable-tariff environment - Stille, Karl Stephan Christian; Böcker, Joachim; Fröhleke, Norbert; Bettentrup, Ralf; Kaiser, Ingo (2016 18th European Conference on Power Electronics and Applications (EPE'16 ECCE Europe))

Supervisional load optimization for households with intelligent domestic appliances - Stille, Karl Stephan Christian; Böcker, Joachim; Fröhleke, Norbert; Bettentrup, Ralf; Kaiser, Ingo (2016 10th International Conference on Compatibility, Power Electronics and Power Engineering (CPE-POWERENG))

The Interplay between Logic and Metaphysics - Ficara, Elena (Hegel and Metaphysics)

Two in One - Ficara, Elena (The Power of Distributed Knowledge)

A Critical Review of Techniques to Determine the Magnet Temperature of Permanent Magnet Synchronous Motors under Real-time Conditions - Wallscheid, Oliver; Huber, Tobias; Peters, Wilhelm; Böcker, Joachim (EPE Journal)

Real-time capable model predictive control of permanent magnet synchronous motors using particle swarm optimisation - Wallscheid, Oliver; Ammann, Ulrich; Böcker, Joachim (PCIM Europe 2016; International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management)

Quantile treatment effects of job loss on health - Schiele, Valentin; Schmitz, Hendrik (Journal of Health Economics)

Public reporting and the quality of care of German nursing homes - Herr, Annika; Nguyen, Thu-Van; Schmitz, Hendrik (Health Policy)

Determinants of regional variation in health expenditures in Germany - Göpffarth, Dirk; Kopetsch, Thomas; Schmitz, Hendrik (Health economics)

Health shocks and risk aversion - Decker, Simon; Schmitz, Hendrik (Journal of Health Economics)

2D analytical model for estimation of eddy current loss in the magnets of IPM machines considering the reaction field of the induced eddy currents - Paradkar, Milind; Böcker, Joachim (2015 IEEE International Electric Machines & Drives Conference (IEMDC))

Voltage controller for flux weakening operation of interior permanent magnet synchronous motor in automotive traction applications - Huber, Tobias; Peters, Wilhelm; Böcker, Joachim (2015 IEEE International Electric Machines & Drives Conference (IEMDC))

Analysis of eddy current losses in the stator windings of IPM machines in electric and hybrid electric vehicle applications - Paradkar, M.; Böcker, Joachim (8th IET International Conference on Power Electronics, Machines and Drives (PEMD 2016))

Comparison of quarter-wave with half-wave symmetrical pulse patterns applied in electrical high-speed drives - Peter, K.; Böcker, Joachim; Mink, F.; Beineke, S. (8th IET International Conference on Power Electronics, Machines and Drives (PEMD 2016))

Comparison of Optimized Pulse Patterns with Direct Model Predictive Control Using Co-Simulation - Schulte, C.; Peter, K.; Böcker, Joachim; Leuer, M. (8th IET International Conference on Power Electronics, Machines and Drives (PEMD 2016))

Inverter loss management for an electrical high-speed drive system - Peter, Klaus; Hanke, Soren; Mink, Fabian; Böcker, Joachim (2016 18th European Conference on Power Electronics and Applications (EPE'16 ECCE Europe))

Sensitivity analysis on production tolerances for electric drive systems in automotive application - Ott, Markus; Böcker, Joachim (2016 18th European Conference on Power Electronics and Applications (EPE'16 ECCE Europe))

Model predictive control strategy for multi-phase thyristor matrix converters — Advantages, problems and solutions - Leuer, Michael; Lönneker, Michael; Böcker, Joachim (2016 18th European Conference on Power Electronics and Applications (EPE'16 ECCE Europe))

Comparison of the performance of gallium nitride (GaN) transistors in a totem-pole power factor controlled (PFC) rectifier - Bolte, Sven; Fröhleke, Norbert; Böcker, Joachim (2016 IEEE International Telecommunications Energy Conference (INTELEC))

Determination of storage loss characteristics with reasonable measurement and calculation effort - Vogt, Thorsten; Pahl, Richard; Fröhleke, Norbert; Böcker, Joachim (2016 18th European Conference on Power Electronics and Applications (EPE'16 ECCE Europe))

Direct Model Predictive Control strategy for multi-phase thyristor matrix converters - Leuer, Michael; Lönneker, Michael; Böcker, Joachim (2015 IEEE International Symposium on Predictive Control of Electrical Drives and Power Electronics (PRECEDE))

DC-DC converter design for power distribution systems in electric vehicles using calorimetric loss measurements - Bolte, Sven; Fröhleke, Norbert; Böcker, Joachim (2016 18th European Conference on Power Electronics and Applications (EPE'16 ECCE Europe))

Numerical optimization of passive line filter components for suppression of electromagnetic interference (EMI) - Henkenius, Carsten; Fröhleke, Norbert; Böcker, Joachim; Figge, Heiko (2016 IEEE Applied Power Electronics Conference and Exposition (APEC))

Efficiency optimization for a power factor correction (PFC) rectifier with gallium nitride transistor - Bolte, Sven; Fröhleke, Norbert; Böcker, Joachim (2015 IEEE 3rd Workshop on Wide Bandgap Power Devices and Applications (WiPDA))

Analysis and design of integrated common and differential mode inductors - Henkenius, Carsten; Fröhleke, Norbert; Böcker, Joachim (2016 IEEE International Telecommunications Energy Conference (INTELEC))

Experimentelle Identifikation eines thermischen Modells zur Überwachung kritischer Temperaturen in hochausgenutzten permanenterregten Synchronmotoren für automobile Traktionsanwendungen - Huber, Tobias

High Power LLC Resonant Converter Optimized for High Efficiency and Industrial Use - Figge, H.

Compact Storage Based Resistance Spot Welding Power Supplies - Dora Venkata Mohana Murali, K,

»Mathematik inklusive«: Lernchancen im inklusiven Anfangsunterricht. - Häsel-Weide, Uta (Beiträge zum Mathematikunterricht. Vorträge auf der 50. Tagung für Didaktik der Mathematik)

Mathematik gemeinsam lernen - Lernumgebungen für den inklusiven Mathematikunterricht. - Häsel-Weide, Uta (Tagungsband des AK Grundschule in der GDM 2016)

"Merit hat 4 von 5 Subtraktionsaufgaben durch Rückwärtszählen gelöst". Leistungsbeurteilung im inklusiven Mathematikunterricht - Häsel-Weide, Uta (Sonderpädagogische Förderung heute)

Vom Zählen zum Rechnen. Struktur-fokussierende Deutungen in kooperativen Lernumgebungen. - Häsel-Weide, Uta

Gemeinsam ordnen – gemeinsam lernen. Mathematische Strukturen sichtbar machen. - Häsel-Weide, Uta (Grundschulunterricht Mathematik)

Schreiberfahrung von Studierenden aus verschiedenen Fächergruppen und deren wahrgenommener Unterstützungsbedarf beim akademischen Schreiben. Ergebnisse einer Querschnittsstudie - Ballweg, Sandra; Kuhn, Carmen; Hertweck, Lisa (Schreibberatung und Schreibförderung. Impulse aus Theorie, Empirie und Praxis)

Portfolios as a means of developing and assessing writing skills - Ballweg, Sandra (Developing and Assessing Academic Writing Skills)

Collective state transitions of exciton-polaritons loaded into a periodic potential - Winkler, K.; Egorov, O. A.; Savenko, I. G.; Ma, Xuekai; Estrecho, E.; Gao, T.; Müller, S.; Kamp, M.; Liew, T. C. H.; Ostrovskaya, E. A.; Höfling, S.; Schneider, C. (Physical Review B)

Talbot Effect for Exciton Polaritons - Gao, T.; Estrecho, E.; Li, G.; Egorov, O. A.; Ma, Xuekai; Winkler, K.; Kamp, M.; Schneider, C.; Höfling, S.; Truscott, A. G.; Ostrovskaya, E. A. (Physical Review Letters)
Keywords: General Physics and Astronomy

Dynamics of exciton-polaritons in discrete lattices under incoherent localized pumping - Yulin, A. V.; Chestnov, I. Yu.; Ma, Xuekai; Schumacher, S.; Peschel, U.; Egorov, O. A. (Physical Review B)

Incoherent control of topological charges in nonequilibrium polariton condensates - Ma, Xuekai; Peschel, Ulf; Egorov, Oleg A. (Physical Review B)

Neu zugewanderte Schülerinnen und Schüler – eine Gruppe mit besonderen Potentialen. Beiträge aus Forschung und Schulpraxis

Unterrichten in Internationalen Förderklassen am Berufskolleg in Nordrhein-Westfalen (NRW) - Frenzel, Beate; Niederhaus, Constanze (Die berufsbildende Schule (68))

„In unserer Schule sind alle im Grunde ins kalte Wasser gesprungen und alle sind nach ´ner Weile belohnt worden durch große Erfolge.“ Interviews mit Lehrerinnen und Lehrern zu den Besonderheiten des Unterrichtens neu zugewanderter Schülerinnen und Schüler - Frenzel, Beate; Niederhaus, Constanze; Peschel, Corinna; Rüther, Ann-Kristin (Neu zugewanderte Schülerinnen und Schüler – eine Gruppe mit besonderen Potentialen. Beiträge aus Forschung und Schulpraxis)

Relevante Sprachmittel für mathematische Textaufgaben – Korpuslinguistische Annäherung am Beispiel Prozentrechnung - Niederhaus, Constanze; Pöhler, Birte; Prediger, Susanne (Deutsch als fremde Bildungssprache: Das Spannungsfeld von Fachwissen, sprachlicher Kompetenz, Diagnostik und Didaktik)

Lehrerinnen und Lehrer für das Unterrichten neu zugewanderter Schülerinnen und Schüler qualifizieren. Zur Qualifizierungsreihe für Lehrkräfte neu zugewanderter Schülerinnen Schüler des Instituts für Deutsch als Zweit- und Fremdsprache der Universität Duisburg-Essen - Niederhaus, Constanze; Schmidt, Eva (Neu zugewanderte Schülerinnen und Schüler – eine Gruppe mit besonderen Potentialen. Beiträge aus Forschung und Schulpraxis)

Integriertes Fach- und Sprachlernen in beruflicher (Anpassungs-) Qualifizierung IFSL: Erzieher*innen, Ingenieur*innen - Niederhaus, Constanze; Havkic, Amra; Schulze, Nina

Friedman, Michael, “Kant on Geometry and Experience”, in: Vincenzo De Risi (Hg.), Mathematizing Space. The Objects of Geometry from Antiquity to the Early Modern Age, Birkhäuser: Cham 2015 (Trends in the History of Science), 275–309 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Rescher, Nicholas und Grim, Patrick, "Beyond Sets. A Venture in Collection-Theoretic Revisionism", ontos Verlag: 2011 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Korpus – Pragmatik – kontrovers - Ptashnyk, Stefaniya (Linguistische Zugänge zu Konflikten in europäischen Sprachräumen)

Historische Sprachkontakte in einer multilingualen Stadt: Beschreibungsprobleme und Desiderate (am Beispiel Lembergs im 19. Jahrhundert) - Ptashnyk, Stefaniya (Historische Sprachkontaktforschung (Jahrbuch für germanistische Sprachgeschichte 7))

Sprachkontakte gestern und heute: Forschungsfragen, methodische Zugänge und Desiderate - Ptashnyk, Stefaniya (Gegenwärtige Sprachkontakte im Kontext der Migration)

Konflikt und Konfliktbewältigung im Spiegel der Sprache, oder: Plädoyer für die Suche nach einem linguistischen Beitrag zur Befriedung Europas - Ptashnyk, Stefaniya; Vogel, Friedemann; Luth, Janine (Linguistische Zugänge zu Konflikten in europäischen Sprachräumen. Korpus – Pragma-tik – kontrovers)

Analyse des Mischverhaltens von Stiftextrudern mit simulativen und experimentellen Methoden - Schöppner, Volker; Schadomsky, Michael; Hopmann, C.; Lemke, F. (KGK Kautschuk Gummi Kunststoffe)

Weyl, Hermann, "Levels of Infinity. Selected Writings on Mathematics and Philosophy, translated and edited with an introduction and notes by Peter Pesic", Dover Publications: Mineola, NY 2012 - Peckhaus, Volker (Mathematical Reviews)

Kennedy, Juliette, “Introduction. Gödel and Analytic Philosophy: How Did We Get Here?” in J. Kennedy (ed.), Interpreting Gödel. Critical Essays, Cambridge Univ. Press, Cambridge 2014, 1–8 - Peckhaus, Volker (Mathematical Reviews)

Manzano, María und Alonso, Enrique, “Visions on Henkin”, In: Synthese 192 (2015), 2123–2138 - Peckhaus, Volker (Mathematical Reviews)

Nawar, Tamar, “Aristotelian Finitism”, In: Synthese 192 (2015), 2345–2360 - Peckhaus, Volker (Mathematical Reviews)

Bringsjord, Selmar und Govindarajulu, Naveen Sundar, “Leibniz’s Art of Infallibility, Watson, and the Philosophy, Theory, and Future of AI”, in: V.C. Müller (Hg.), Fundamental Issues of Artificial Intelligence, Springer: Cham 2016 (Synthese Library; 376), 183–200 - Peckhaus, Volker (Mathematical Reviews)

Silvestri, Giuseppe, “The Analogies and Confirmations of Peano’s Solution of the Antinomies in the Later Authors: Behmann (1957), Dumitriu (1968), Priest (1994)”, In: Metalogicon n.s. 1 (2016), 1–30 - Peckhaus, Volker (Mathematical Reviews)

Gegenwärtige Sprachkontakte im Kontext der Migration - Ptashnyk, Stefaniya (Rezensiert von: 1) Pecht, Nantke, in: Zeitschrift für Rezensionen zur germanistischen Sprachwissen-schaft. Heft 2/2018 (online veröffentlicht am 12/06/2018). 2) Page, Richard B., in: Yearbook of German-American Studies 52 (2017), S. 311–314. 3) Langer, Nils, in: Modern Language Review, Nr. 4/2019, p. 896–898.)

Schreiben eine Stimme geben. Über die Beziehung von lautem Sprechen und Schreiben im Schreibprozess - Lohmeier, Yvonne; Karsten, Andrea (JoSch – Journal der Schreibberatung)
Keywords: Schreibberatung; Schreibdidaktik; Schreibprozess; Sprache

Renegotiable vs. Non-Renegotiable Agreements - Theory and Applications - N, N

Wie wertvoll ist der Einzelne für das Team? - Performancemessung der Bundesligaspieler anhand der kooperativen Spieltheorie der Saison 2014/2015 - N, N

Automatisiertes Matching von Angebot und Nachfrage in der Kunststoffindustrie Ein Fallbeispiel in Kooperation mit der PINPOOLS GmbH - N, N

Der Einfluss von Netzwerken auf Gleichgewichtspreise - eine spieltheoretische Analyse - N, N

Hat vertikale Integration einen Einfluss auf die allgemeine Wohlfahrt? - N, N

Stabile Supply-Chains - Basierend auf der Theorie der Matching-Märkte - N, N

Die Berechnung von Machtindizes - ein Vergleich verschiedener Verfahren - N, N

Intermediaries in Buyer Seller Networks - N, N

Staatliche Regulierung in vertikal verbundenen Industrien - eine spieltheoretische Analyse - N, N

Pricing and Revenue Sharing of Bundles Using Game Theoretical Concepts - N, N

Paul Maar. Bielefelder Poet in Residence 2015 / Paderborner Kinderliteraturtage 2016

Philosophinnen in der Schule - Hagengruber, Ruth (Ethik/Philosophie Didaktik. Praxishandbuch für die Sekundarstufe I und II)

The Long-Lasting Tradition of Women Philosophers as an Insight into the History of Ideas - Hagengruber, Ruth Edith (Materials of the Inter-University Scientific Conference with International Participation)

Augenscheinlich und ohrenkundig. Bilderbuch-Hörspiel-Medienverbünde und ihr intermediales Potenzial für ästhetisches Lernen - Kruse, Iris (Im Bildungsfokus. Bilderbuchforschungsrezeption)

Kinderliterarische Medienverbünde im inklusiven Literaturunterricht der Grundschule - Mediale Darstellungsvielfalt als Chance für gemeinsame literarästhetische Erfahrungen - Kruse, Iris (Der inklusive Blick. Die Literaturdidaktik und ein neues Paradigma)